(untitled) (Revista Cientifica Ingenio Magno, 2022)
This article presents the results of the study that sought to determine the consumption preferences of Hass avocado oil in the cities of Bogotá, Tunja, Bucaramanga and Villavicencio (Colombia), it was carried out through a non-experimental exploratory cross-sectional design taking into account He says that the objective was to obtain a panoramic view of people’s interest in avocado oil products, and identify possible uses and aspects for the development of the product, for which an information collection instrument focused on the supply was designed, demand and price for Hass avocado oil, the population size of this study was 8.465.949, the sample size is 1,872. A very favorable aspect was observed at a general level, such as the great possibility of substituting the different oils that are commonly used with the use of avocado oil, for nutritional purposes (72%), pharmacological use (45%), cosmetic use (57 %) uses as a dressing (75%), in fried foods (63%) and in food cooking (78%). The price that they would be willing to pay for 100mL of avocado oil is in the range of 10.000 to 15.000; 98% of the respondents indicated their interest in the use of avocado oil.